Do Medicine and Medical Education Need a Paradigm Shift? - Hermanto TJ (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Modern medicine stands at a crossroads. The Human Genome Project and the Decade of the Brain have revealed the profound biological and neurological individuality of every human being. Yet paradoxically, clinical practice and medical education continue to operate as if one method fits all. Patients are often reduced to diagnostic codes and treatment algorithms, while students are molded through standardized curricula, uniform assessments, and teacher-centered instruction. The result is a dissonance between what science now knows, that every brain and body is unique, and how medicine is still practiced and taught. Half a century ago, Ivan Illich, in Medical Nemesis, warned of the medicalization of life where health becomes a commodity and suffering a pathology. Today, his warning resounds in the rising prevalence of iatrogenic conditions, from overtreatment to complex disorders such as placenta accreta syndrome. Bernard Lown in The Lost Art of Healing, lamented the erosion of empathy, while Atul Gawande’s Being Mortal reminds us that extending life is not the same as healing it. These critiques echo Sir William Osler’s timeless insight: that the good physician treats the disease, but the great physician treats the patient who has the disease.